DECISION SUPPORT SYSTEM FOR DETERMINING APPROPRIATE FRANCHISE LOCATIONS USING THE PROFILE MATCHING METHOD - Tati Mardiana; Yesni Malau (Jurnal Riset Informatika, 2020)
Finding the appropriate location is crucial when starting a franchise. The appropriate location will affect the overall business risk and profitability of the franchise. Nevertheless, some franchises have a bankruptcy in running their business. One of the factors that contribute to the bankruptcy of a franchise business is a location that does not meet several criteria that support business success. Therefore, this study aims to propose a decision support system model to determine the location of the franchise based on matching profiles between the actual data value of a location and the value of the location profile expected by the franchisor. The profile matching method has a better level of objectivity because it measures the value of each indicator variable. The criteria for determining the location of a franchise are potential customers, access to location, competition, and costs. The test results show that the decision support system to determine the location of the franchise using the profile matching method meets the functional requirements. This decision support system helps franchises to determine the appropriate when starting a franchise.